Effect of Process Parameters on Repeatability Precision of Weight for Microinjection Molding Products - Quan Wang; Jinrong Wang; Chongying Yang; Kaihui Du; Wenli Zhu; Xiaoli Zhang (Advances in Polymer Technology)
The repeatability precision of weight for injection molded products is important technical parameter to measure the quality and accuracy of injection molded products and evaluate the performance of injection molding machine. The influence of mold temperature, melt temperature, packing pressure, and packing time on the weight of microinjection molding products was studied by Taguchi orthogonal experiment. The influence of peak cavity pressure on the weight of products also was analysed. The experimental results show that the packing pressure is the most important process parameter affecting both the weight of the tensile and the impact specimens. With the increase of the packing pressure, the weight of the tensile and the impact specimens increases. When the peak cavity pressure reaches a certain value, the pressure value of the tensile specimen is 65 MPa, and the pressure value of the impact specimen is 68 MPa, the weight of the product increases quickly. The packing pressure increased from 85 MPa to 100 MPa, the weight of the tensile specimen increased from 0.544g to 0.559g, an increase of 2.7%, and the weight of the impact specimen increased from 0.418g to 0.425g, an increase of 1.7%.